1985
DOI: 10.1177/001440298505100601
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Employment Status of Handicapped Youth Exiting High School from 1979 to 1983

Abstract: Factors associated with the employment status of handicapped youth were investigated in a sample of 462 youths from nine Vermont school districts. All students from these districts who exited high school between 1979 and 1983, and who had been receiving special education services, were identified. Interviews were conducted with 301 youths to solicit current employment status, employment and training history, and use of social services. Additional information regarding educational history, age, and community de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
178
5
7

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(199 citation statements)
references
References 11 publications
9
178
5
7
Order By: Relevance
“…Female students have been found to be less likely than their male counterparts to take courses in agricultute and industry, and they are more likely to receive training in home economics, health care, and clerical jobs (Blackorby, 1993;Wagner, 1992). Researchers also have found that young women with disabilities exit school with less wotk experience than young men with disabilities (Doren & Benz, 1998;Hasazi, Gordon, & Roe, 1985;Wagner), which may contribute to underemployment and unemployment as adults.…”
Section: Winter 2008mentioning
confidence: 99%
“…Female students have been found to be less likely than their male counterparts to take courses in agricultute and industry, and they are more likely to receive training in home economics, health care, and clerical jobs (Blackorby, 1993;Wagner, 1992). Researchers also have found that young women with disabilities exit school with less wotk experience than young men with disabilities (Doren & Benz, 1998;Hasazi, Gordon, & Roe, 1985;Wagner), which may contribute to underemployment and unemployment as adults.…”
Section: Winter 2008mentioning
confidence: 99%
“…In Vermont, Hasazi and her colleagues reported that 34% of mildly handicapped public school youth were not completing a high school education (Hasazi, Gordon, & Roe, 1985). The reported dropout rate of handicapped youth in several school districts in Florida was pegged at 31 % (Fardig, Algozzine, Schwartz, Hensel, & Westling, 1985).…”
Section: Dropout Ratementioning
confidence: 99%
“…The probability of future employment for students with disabilities decreases over time. For part-and full-time work combined, most studies report about a 60% employment level for persons with disabilities (Hasazi, Gordon, & Roe, 1985; Wagner, 1989Wagner, , 1991. Also, according to data provided by NTLS (1990), only 1.8% of the graduating students with learning disabilities go to four-year universities.…”
Section: Introductionmentioning
confidence: 99%